MO434: Bemcentinib Targets Macrophage and Mesangial Cells in Renal Fibrosis. (3rd May 2022) - Magnus Grøndal, Sturla; Hodneland Nilsson, Linn; Blø, Magnus; Boniecka, Anna; Milde, Eline; Jackson, Akil; Gausdal, Gro; Lorens, James B
Abstract: BACKGROUND AND AIMS: Renal fibrosis, a progressive process of extracellular matrix accumulation leading to renal failure, lacks effective treatment. Expression of the AXL receptor tyrosine kinase has been implicated in kidney injury and mesangial proliferation [1 ]. Inhibition of AXL signalling with the selective AXL kinase inhibitor bemcentinib reduces fibrosis and inflammation in murine models of unilateral ureteral obstruction (UUO) and in glomerulonephritis [2, 3 ]. METHOD: Male C57Bl/6 mice were subjected to UUO for 3 or 15 days and treated twice daily with vehicle or bemcentinib (50 mg/kg) by oral gavage. Kidneys were divided into pieces that were either dissociated into single cells for mass cytometry analysis or subjected to Sirius Red staining to evaluate collagen deposition. Samples for mass cytometry were stained with a 45-plex antibody panel, acquired on Helios, then cleaned and analysed using UMAP [4 ] for dimensionality reduction and PARC [5 ] for clustering. The effect of ligation was modelled with the least absolute shrinkage and selection operator (LASSO) using centered log-ratio transformed cluster compositions to predict the number of days of ligation. LASSO is a regression method that prevents overfitting by penalizing variables and is commonly used for variable selection. RESULTS: Sirius Red staining confirmed, as previously published, reduced fibrosis development in kidneys from bemcentinib treated animals compared to the vehicle following 15 days of UUO. No significant effect of bemcentinib was observed after 3 days of obstruction. Mass cytometry analysis yielded 31 clusters representing immune, endothelial, pericyte, mesangial and epithelial cells from proximal tubules, loop of Henle, distal tubules and collecting duct. AXL was expressed by pericytes, endothelial cells, mesangial cells and macrophages. Modelling with LASSO suggested that the most important feature of ligation was the expansion of mesangial cells. Bemcentinib treatment did not result in any significant changes in non-ligated kidneys and kidneys ligated for 3 days. At 15 days, post-bemcentinib treatment, the number of mesangial cells and macrophages decreased, while the number of epithelial cells comprising the proximal tubules and loop of Henle increased. The LASSO model estimation corresponded to an apparent reduction in disease progression of 30% (corresponding to day 10 or 11 post-ligation). CONCLUSION: AXL targeting macrophages and mesangial cells delays the progression of kidney fibrosis in the UUO model and represents a valid approach to treat kidney disease. References : 1. Yanagita M, Arai H, Ishii K. et al. Gas6 regulates mesangial cell proliferation through Axl in experimental glomerulonephritis. Am J Pathol. 2001; 158: 1423–1432. 2. Landolt L, Furriol J, Babickova J. et al. AXL targeting reduces fibrosis development in experimental unilateral ureteral obstruction. Physiol Rep. 2019; 7: e14091. 3. Zhen Y, Lee IJ, Finkelman FD. et al . Targeted inhibition of Axl receptor tyrosine kinase ameliorates anti-GBM-induced lupus-like nephritis. J Autoimmun. 2018; 93: 37–44. 4. McInnes L, Healy J, Melville J. Umap: Uniform manifold approximation and projection for dimension reduction. arXiv preprint arXiv:180 203 426. Published online 2018. 5. Stassen SV, Siu DMD, Lee KCM. et al . PARC: ultrafast and accurate clustering of phenotypic data of millions of single cells. Bioinformatics . 2020; 36: 2778–2786.